2022
DOI: 10.3892/ol.2022.13424
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin inhibits the proliferation of cervical cancer cells via FAK/AKT/GSK3β signalling

Abstract: Cervical cancer is one of the most lethal malignancies of the female reproductive system. Shikonin, a naphthoquinone pigment extracted from the traditional medicinal herb, Lithospermum erythrorhizon, has been demonstrated to exert significant inhibitory effects on a variety of tumours in vitro and in vivo. In the present study, the effects of shikonin on cervical cancer and the underlying mechanisms were investigated. The effects of shikonin on the viability on HeLa and SiHa cervical cancer cells was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Studies have confirmed that many tumors, such as gastric and colorectal cancer, have a high expression of GSK3β 47 . In addition, a large number of studies have shown that in CC, GSK3β is involved in the regulation of the PI3K/Akt signaling pathway and the promotion of the malignant progression of CC cells 48,49 . This suggests that the regulatory role of USP14 in CC progression may be due to interactions with different key signaling pathways.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies have confirmed that many tumors, such as gastric and colorectal cancer, have a high expression of GSK3β 47 . In addition, a large number of studies have shown that in CC, GSK3β is involved in the regulation of the PI3K/Akt signaling pathway and the promotion of the malignant progression of CC cells 48,49 . This suggests that the regulatory role of USP14 in CC progression may be due to interactions with different key signaling pathways.…”
Section: Discussionmentioning
confidence: 91%
“…47 In addition, a large number of studies have shown that in CC, GSK3β is involved in the regulation of the PI3K/Akt signaling pathway and the promotion of the malignant progression of CC cells. 48,49 This suggests that the regulatory role of USP14 in CC progression may be due to interactions with different key signaling pathways. The pathway of USP14 action in CC may be a type of network rather than a single upstream and downstream pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Among the phytochemicals, the biological activities of shikonin and its natural derivatives have been widely explored in the past decade. Shikonin exhibits a variety of biological activities through different targets and molecular pathways, including inhibition of Epstein-Barr virus reactivation through NLRP3 downregulation, 29 suppression of cervical cancer cell proliferation through FAK signaling pathway, 30 and induction of necroptosis in NPC cells through ROS and RIPK1/ RIPK3/MLKL upregulation. 31 Recently, functional activities and targets of novel synthetic shikonin derivatives for colorectal cancer treatment are also evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of Shikonin against a range of systemic malignancies has been thoroughly investigated, encompassing lung cancer, lymphoma, leukemia, gastric cancer, colorectal cancer, hepatocellular carcinoma, pancreatic cancer, and breast cancer ( Tang et al, 2018 ; Guo et al, 2019b ; Ji et al, 2022 ; Li et al, 2022 ; Xu et al, 2022 ; Dong et al, 2023 ; Király et al, 2023 ; Qian et al, 2023 ; Zhang et al, 2023 ). Shikonin is rich in various chemical constituents, including naphthoquinones, flavonoids, phenolic acids, terpenes, and polysaccharides.…”
Section: Shikonin’s Anti-cancer Mechanism Targeting Rosmentioning
confidence: 99%